2009
DOI: 10.1007/s00038-009-5405-9
|View full text |Cite
|
Sign up to set email alerts
|

The Health Behaviour in School-aged Children (HBSC) study: methodological developments and current tensions

Abstract: While these challenges are not trivial, the structure of the HBSC network and its long-term experience in working through such challenges renders it likely that HBSC can provide a model of other similar studies facing these tensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
545
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(581 citation statements)
references
References 26 publications
3
545
0
14
Order By: Relevance
“…The participation of the community is one of the requisites for classifying a school as a health promoter. 14,19 In this study, the majority of managers referred that parents and employees were involved in the meetings and actions regarding health and healthy eating topics. However, the average number of meetings was considered low when compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participation of the community is one of the requisites for classifying a school as a health promoter. 14,19 In this study, the majority of managers referred that parents and employees were involved in the meetings and actions regarding health and healthy eating topics. However, the average number of meetings was considered low when compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 This model oriented on the choice and adaptation of the variables. For each component and/or subcomponent the necessary structure (human and material resources) were specified, as well as the adequate process (actions to be executed), aiming short and medium term results which would lead, in long term, to the reduction of obesity and its cardiovascular complications (Figure1).…”
Section: Methodsmentioning
confidence: 99%
“…The recommended sample size for each of the three age groups was approximately 1 500 students, assuming a 95 % confidence interval of +/-3 percent around a proportion of 50 per cent and allowing for the clustered nature of the samples. Further details of the study's development and methods employed can be found in this supplement and elsewhere [21][22][23] .…”
Section: Methodsmentioning
confidence: 99%
“…in the comparisons between countries. Further information in this respect can be found in Roberts et al (2009).…”
Section: Procedures and Statistical Analysesmentioning
confidence: 99%